Analisis Risiko Sanitasi dan Kejadian Penyakit Kulit di Kecamatan Medan Belawan Kota Medan - Malau, Pitto Malau; Naria, Evi; Indirawati, Sri Malem (Jurnal Kesehatan Komunitas, 2024)
Introduction: Skin diseases are among the most common ailments found in tropical countries. According to BPS data 2019, skin diseases were ranked among the top 10 diseases in Medan City. Based on disease data from the Medan Belawan Health Center, skin diseases were among the top 10 highest diseases from 2022 to 2023, with 1,751 cases and a percentage of 24 percent. According to data and observations, many households still lack access to complete basic sanitation that meets health standards, one of which is wastewater disposal systems (SPAL). The majority of household SPALs are open and pollute the environment. Methods: his study aims to analyze the sanitation risk of wastewater disposal system variables with the incidence of skin diseases. The population consists of 27,114 households, with a sample size of 100 households. The study was conducted from December 2023 to June 2024. Data were collected through interviews using a questionnaire, which were then calculated using the Sanitation Risk Index (IRS) formula to obtain a score indicating sanitation risk. A chi-square statistical analysis was used to assess the relationship between wastewater disposal system variables (SPAL) and the incidence of skin diseases. Results/Finding: The statistical analysis results showed a relationship between wastewater discharge and the incidence of skin diseases with a p-value = 0.028 and an Exp-B value of 4.01.  Based on the research results, the wastewater sewer sanitation risk index is in the very high-risk category, with a score index of 67. A relationship between wastewater discharge and skin disease incidence was obtained based on statistical analysis (p-value 0.028, prevalence ratio = 1.7). The management of household SPAL needs to be improved, namely with the type of SPAL that is closed/meets health requirements and does not cause environmental pollution.